The Relationship Between Utilization of Discount Coupons on Online Food Delivery Applications with Obesogenic Intake and Obesity Among Nutrition Health Students at Gadjah Mada University - Aureally, Thyssa Ariany; Budiningsari, Dwi; Kusumaningrum, Fitrina (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to determine the relationship between the utilization of discounts on online food delivery applications and obesogenic intake as well as obesity nutritional status among students of the Health Nutrition Study Program at Gadjah Mada University. Methods: This research is an observational study that employs a cross-sectional design. The research involves 80 active students who have used online food delivery applications over the last three months and reside in Yogyakarta as of February 2024. The dependent variable is the utilization of discounts. Independent variables are obesogenic intake and obesity status. Confounding variables are respondents' education duration in the Health Nutrition Study Program, pocket money, place of residence, and duration of sleep. The sampling technique used is proportionate stratified random sampling, and the statistical tests used are the Chi-Square test and the Mantel-Haenszel test to control for confounding variables. Results: The utilization of discounts is associated with the frequency of obesogenic intake (p-value: 0.000). The utilization of discounts is not associated with obesity status (p-value: 0.617). Conclusion: There is a relationship between the utilization of discounts and obesogenic intake both before and after being controlled for the duration of education in the Health Nutrition Study Program, pocket money, and place of residence. There is no relationship between the utilization of discounts and obesity status both before and after being controlled for the duration of education in the Health Nutrition Study Program, pocket money, and sleep duration. The restaurant should provide menu options and information on sodium, sugar, and fat for each food and drink available. Subsequent researchers are advised to investigate variables that have not yet been studied, such as stress levels, peer influence, parents' occupations, and incidents of weight gain or overweight.